Dynamic power allocation of battery-supercapacitor hybrid energy storage for standalone PV microgrid applications. (August 2017) - Jing, Wenlong; Lai, Chean Hung; Wong, Wallace S.H.; Wong, M.L. Dennis
Abstract: Standalone photovoltaic-based microgrid with energy storage system could be a promising solution for powering up off-grid communities. One of the major issues that hinder the development of standalone microgrids is the poor service life of the batteries. To address this issue, hybrid energy storage systems (HESS) and novel power management strategies have been proposed by researchers to enhance the service life of battery bank. This paper presents a novel multi-level hybrid energy storage system topology and its associated power management strategy to mitigate the charge/discharge stress on battery. Matlab Simulink model of typical standalone PV microgrid with different HESS topologies are developed to evaluate the performance of the proposed system. Actual solar irradiance data with different weather conditions and estimated load profile based on site survey results are used to analyze the effectiveness of different HESS in mitigating stress on batteries. A comprehensive analysis and benchmarking is presented to compare the technical and financial viability of the proposed system with existing HESS solutions. Simulation results show that the proposed HESS can improve the life expectancy of the battery and reduce the operating cost of the standalone PV-battery microgrid.